ANALISIS KLASTER DURIAN (Durio zibethinus Murr.) UNGGUL LOKAL DI KABUPATEN JEMBER DAN BANYUWANGI - Vega Kartika Sari; Eva Rosdiana; Sepdian Luri Asmono (Jurnal Agroteknologi, 2021)
Indonesia is one of the centers of durian diversity in the world and one of the regions that makes durian a superior local fruit crop is Jember and Banyuwangi. Clustering is useful to facilitate the search for certain features of the type of durian. This study aims to determine the durian grouping in two districts namely Jember and Banyuwangi. The materials used were local superior durian fruit and characterization questionnaire. Research using descriptive methods. Characterization data will be analyzed using NTSYS software.The results showed that local superior durian fruit were grouped into 2 groups based on morphological characters. Cluster 1 consists of 4 durians namely Klemben, Hijau, Bajul, and Lambau. Cluster 2 only consists of durian Musang King. Based on the chemical content of durian fruit, durian Lambau from Jember has the highest water content of 75.52%, Musang King from Banyuwangi has a fat content (2.29%), Bajul from Jember has the highest fiber content (11.89%), and Hijau from Banyuwangi has the highest protein (3.14%) and sugar (26.08%) content. Based on PCA showed that Musang King and Hijau have similirity on some morphological characters and chemical fruit contents. The results of correlation analysis of morphological characters and chemical content of durian fruit showed that leaf length was positively correlated with leaf width and protein content. Leaf width is positively correlated with sugar content. Fruit weight is positively correlated with water content.